Operation University: The Formation of the National Federation of Catholic College Students, 1937–1950 - Ahern, Kevin J. (US catholic historian, 2022)
For over thirty years, the National Federation of Catholic College Students (NFCCS), an affiliate of the International Movement of Catholic Students (IMCS-Pax Romana), offered students at U.S. Catholic colleges and universities both a vision of an active student apostolate and a vehicle for exercising apostolic agency. As an organization in the tradition of specialized Catholic Action, the NFCCS promoted activity by students in their own milieu. This included forming representative student governments, promoting social and interracial justice, developing national and international structures to address student concerns, and mobilizing over $500,000 to aid fellow students displaced by World War II. This article examines the federation’s work from its foundation in 1937 to 1950, the halfway point in its organizational life. Mid-century began a new chapter of mobilization, particularly as the student generation that the Second World War directly shaped completed their studies and their time with the organization.